The Influence of Product Quality, Brand Image, and Online Consumer Review on Purchasing Decision for The Originote Products - Febrianti, Esa Rahmah; Utami , Restu Frida; Rahayu, Tri Septin Muji; Purnadi, Purnadi (East Asian Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of product quality, brand image, and online consumer reviews on purchasing decisions. This research approach uses quantitative. The sample used was 100 respondents taken based on the purposive sampling technique. Tests include descriptive statistical tests, validity tests, reliability tests, and classical assumption tests, including normality tests, multicollinearity tests, and heteroscedasticity tests. The next test is the model fit test, multiple regression analysis, hypothesis testing, and the coefficient of determination R2. The study's findings show that decisions about what to buy are posively and significantly influenced by brand perception, and positively but no significantly ifluenced by online consumer reviews The Originote product is a beauty product from China. These findings imply that new brands like Originote should focus on improving product quality and branding strategies. Although online consumer reviews are currently playing less of a role in purchasing decisions, they are still crucial for long-term reputation. This finding provides direction for corporate strategy.